2017
DOI: 10.1002/rsa.20727
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing a graph into expanding subgraphs

Abstract: A paradigm that was successfully applied in the study of both pure and algorithmic problems in graph theory can be colloquially summarized as stating that any graph is close to being the disjoint union of expanders. Our goal in this paper is to show that in several of the instantiations of the above approach, the quantitative bounds that were obtained are essentially best possible. Three examples of our results are the following:• A classical result of Lipton, Rose and Tarjan from 1979 states that if F is a he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
(141 reference statements)
0
11
0
Order By: Relevance
“…We mention that this bound is far from tight and indeed, without too much effort, it can be shown that the number of cycles of length s in Q d is at most 2 d sd 2 s 2 (see [39,Claim 3.2]).…”
Section: Property (Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…We mention that this bound is far from tight and indeed, without too much effort, it can be shown that the number of cycles of length s in Q d is at most 2 d sd 2 s 2 (see [39,Claim 3.2]).…”
Section: Property (Ii)mentioning
confidence: 99%
“…In fact, it is perhaps surprising that the expansion properties of L 1 Q d p are useful at all, since random subgraphs of the hypercube have been used by Moshkowitz and Shapira [39] to construct graphs which have in some way the worst possible expansion properties.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the regularity condition is crucial for proving Theorem 3. The following theorem was proved in [29]. Theorem 4 ([29]).…”
Section: A Regular Non-expanding Graphmentioning
confidence: 99%
“…We note that each of the parameters in Theorem 3 is essentially optimal (see [29] for further discussion).…”
Section: For Every T-vertex Subgraph H Of G That Is Not a Forestmentioning
confidence: 99%
“…It is well known that any graph can be decomposed into connected components of conductance Ω(ǫ/ log n) (and hence poly(ǫ −1 , log n) mixing time) after removing at most an ǫ-fraction of the edges [5,33,39,41]. Moshkovitz and Shapira [31] showed that this bound is essentially tight. In particular, removing any constant fraction ǫ of the edges, the remaining components have conductance at most O((log log n) 2 / log n).…”
Section: Introductionmentioning
confidence: 99%